Homomorphic encryption security - a review - Phani Prasad, J.; Seetha Ramulu, B.; Amarnatha Reddy, E. (International Journal of Engineering and Technology, 2018)
As the Data and Technology is increasing exponentially the security and privacy issues are becoming a major concern in the present scenario, lot of security mechanisms are in to real time and practice, but even there are some bottlenecks with the existing security techniques. In this work we are giving the essence and importance of an encryption scheme called homomorphic encryption and its related issues.Â